Revisiting the Value Education in the Field of Primary Education - Ahmad Shofiyuddin Ichsan (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to describe the thoughts of Abdurrahman An-Nahlawi in education, how the educational methods are used, and what is the relevance of An-Nahlawi's educational thinking in revisiting value education of the primary education in Indonesia. This research is qualitative research with a type of library research, while the approach used is discourse analysis. The results obtained are that to develop the potential of students to create value education, An-Nahlawi offers six varied learning methods sourced from the scriptures (the Qur'an and Hadith). An-Nahlawi also requires that education must be tiered. An-Nahlawi emphasizes that education is a shared task or responsibility, namely the school environment, the community environment (including student’s digital social environment), and the family environment. Therefore, herein lies the relevance of the value education concept on An-Nahlawi’s perspective with primary education in Indonesia, especially in the context of the current millennial era. Keywords: Value Education, Primary Education, Abdurrahman An-Nahlawi